Strengthening the Capacity of BUMDes Astaguna Trihanggo Village in Facing the Industrial Revolution 4.0 - Juhari Sasmito Aji; Reza Widhar Pahlevi; Kemala Hayati (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
The implementation of community service regarding strengthening the capacity of the establishment of Village-Owned Enterprises (BUMDes) Astaguna in facing the Industrial Revolution 4.0 aims to realize information and communication technology in managing BUMDes operations; it is intended to provide BUMDes with a survival strategy for competitors. The renewal effort is motivated by the social behaviour of society, which is dependent on technological developments, marked by the Industrial Revolution, which disrupted multi-fields and had a global impact. The implementation time was held in the Even Semester of 2023 for 30 days from January 1, 2023, to January 30, 2023. Implementing the service begins with planning, activities, and evaluation involving the partner group as the subject and object of service. The conclusion of the service implementation is the impact of increased understanding, which is realized in BUMDes operational activities, which include BUMDes digitalization, which focuses on providing awareness of digital marketing strategies. Then, there is a business plan preparation using the canvas model and SWOT formulation to find BUMDes strategies, then compiling BUMDes governance to be implemented according to the principles of transparency and accountability.